Rynek krajowy baraniny na tle standardów Unii Europejskiej: The domestic market lamb against a background of the standards of the European Union - Pieniak-Lendzion, Krystyna; Nowogródzka, Teresa; Horoszewicz, Elżbieta; Niedziółka, prof. UPH, Roman (Management and Administration Journal, 2021)
Mutton is the only species of meat in the European Union, whose production does not cover the needs of the internal market, and it is necessary to import it. Self-sufficiency in mutton is estimated at approximately 8o%. The mutton market in the EU is a niche available for Polish producers. Lamb production in Poland in 2011 was 3.6 thousand tones. For many years Polish lamb consumption has remained at a very low level compared to the trends in other European Union countries. Therefore Polish sheep production mainly depends on foreign markets, including the possibility to export slaughter- lambs to the market of the European Union.